Field notes contributed by Paul Martsching, spring 1983 - Martsching, Paulet al (1983)
Spring report of birds found in Story County contributed by Paul Martsching. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1983. Epson - sheet feed